Emergence of Money as a Medium of Exchange: An Experimental Study - Duffy, John; Ochs, Jack (American Economic Review, 1999)
This paper reports findings from an experiment that implements a search-theoretic model of money as a medium of exchange. The question examined is whether subjects learn to adopt the same commodities as media of exchange that the model predicts will be used in equilibrium. We report that subjects have a strong tendency to play “fundamental” rather than “speculative” strategies even in environments where speculative strategies yield higher payoffs. We examine some possible motivations for subjects' behavior and conclude that subjects are mainly motivated by past payoff experience as opposed to the marketability considerations that the theory emphasizes. (JEL D83, E40)